The impact of technological change and automation on income distribution and labor income share: A bibliometric analysis (1975–2024) - Vallerie Peter; Assis Kamu; Lim, Beatrice Fui Yee; Ho Chong Mun (Research and Innovation in Social Science, 2025)
Recently, topics regarding the link between technological advancement, automation, income distribution and labor income share have been receiving much attention. However, a comprehensive bibliometric analysis of this field has yet to be conducted. Hence, this paper aims to fill that gap by examining the development and trends in research focusing on automation, technological change, and their impact on income distribution and labor income share. Bibliometric data sourced from the Scopus database were used, covering articles published between 1975 and 2024 based on several predefined criteria. The analysis was performed using Bibliophagy, incorporating a total of 509 articles. A significant increase in annual publications was observed from 2010 to 2024. The United States and China were the dominant countries in this field, accounting for 14.15% (72 articles) and 10.61% (54 articles) of the publications, respectively. Besides that, University of California and Daron Acemoglu were identified as the most influential institution and author, respectively. Technological Forecasting and Social Change journal stands out as the most prolific source with 19 publications in this field, while the Journal of Development Economics has garnered the most citations. Key terms such as "technological change” and "income inequality" were frequently used by authors, with thematic trends indicating a growing focus on “automation” and “artificial intelligence”. These findings reflect an increasing academic and policy-driven interest in understanding how technological disruption reshapes labor markets. Overall, this study provides an overview of the most influential publications, authors, countries, and topics in the field, shedding light on the evolving research landscape surrounding the intersection of technological change and labor market dynamics.